Reading aloud as performance and its representation on television programmes for children. Issue 4 (7th August 2016) - Zhang, Kunkun; Djonov, Emilia; Torr, Jane
ABSTRACT: The social practice of reading aloud picture books to children, or shared reading, has been represented on many televisions programmes broadcast across English-speaking countries. This article views shared reading as a performance, and explores its transformation on two television shows for children and the potential of such shows to promote reading engagement and literacy development. Taking a critical multimodal perspective, we analyse shared reading in real life and on television as a social practice, focusing on the ways the participants talk about the picture book, relate it to exterior texts or activities, and legitimise shared reading through the employment of multimodal and interactive strategies. The analysis reveals significant differences between actual adult–child shared reading and its representation on television. The comparison illustrates the potential benefits and limitations of television shows in which picture books are read to the viewer, in terms of promoting shared reading among families and supporting young children's emergent literacy development.